Measurement and determinants of health poverty and richness: evidence from Portugal - Simões, Nádia (2013)
The analysis of health inequalities is a critical topic for health policy. With data for Portugal, we propose a procedure to convert information provided by the official National Health Survey to EuroQol. Based on these data, we make two contributions. First, we extend measures and methods commonly applied in other fields of economic research in order to quantify the phenomena of health poverty, richness, and inequality. Second, using an ordered probit model, we evaluate the determinants of health inequalities in Portugal. The results show that there is a remarkable level of health inequality, with significant rates of poverty (11.64%) and richness (22.64%). The econometric study reveals that gender, age, education, region of residence, and eating habits are among the most critical determinant factors of health.